Prevalence of leptospira species in waterand soil in six states of Peninsular Malaysia and the pathogenicity of L. hebdomadis - A. Rashid, Fairuz Ridzlan (2011)
Leptospirosis is recognized as one of the important zoonotic diseases in the world including Malaysia. The tropical condition and rainy season in Malaysia favour the growth of leptospires and have potentially cause leptospirosis outbreak. Overall, a total of 902 water samples and 231 soil samples were collected from selected places in Peninsular Malaysia. The water and soil samples were filtered and inoculated into semisolid Johnson-Seiter (JS) medium, incubated at room temperature and in dark condition for 2 months. The cultures were examined under the dark-field microscope for growth of leptospires. A series of characterization such as 8-Azaguanine Inhibition Test, Polymerase Chain Reaction (PCR) assay and serogrouping by Microscopic Agglutination Test (MAT) were done to the isolates to identify whether they are pathogenic leptospires. Among the leptospiral isolates, one isolate was selected to study its pathogenicity in hamster model. Giemsa stain, bacterial culture, serological examination, PCR assay and histopathology of target organ were done to determine the pathogenicity of the isolate to the animal model. A total of forty-three cultures (3.8%) exhibited positive growths which were seen under dark field microscope. The positive cultures were from 39 water and 4 soil samples. Among leptospiral isolates, only 21% (9/43) were confirmed as pathogenic spp. based on 8-Azaguanine Test and PCR. Serogrouping of the isolates with MAT showed that hebdomadis was the dominant serovar in 4 isolates. In the experimental animal study, growth of leptospires was not seen in all bacterial cultures. However, through PCR assay, leptospires were detected in blood and kidney samples at Day 5 post inoculation. Besides that, the antibody titre produced against the isolate was at 1:160. Histologically, selected isolates produced hemorrhagic glomerulitis, tubulointerstitial nephristis, and necrosis in hepatic and splenetic cell. In conclusion, the results demonstrated that pathogenic leptospires can be detected in Malaysian environment and an isolate obtained can cause leptospiral infection to hamsters. Understanding the prevalence of leptospirosis is important to target the sources of contamination and risk activities associated at reside places can be prevented.